Price disorder and information content in energy and gold markets: The effect of the COVID-19 pandemic - Salim Lahmiri (Energy Nexus)
In this paper, we examine market efficiency in fossil energy and gold markets. Specifically, we study price disorder and information content in various energy markets and in gold market before and during the COVID-19 pandemic. The set of energy markets include West Texas Intermediate (WTI), Brent, natural gas, heating oil, and gasoline. For each market, we estimated the correlation dimension, Lyapunov exponent, and approximate entropy for periods before and during the pandemic. In this regard, we contribute to the literature by using different nonlinear features to provide a rich description of the nonlinear dynamics in price evolution before and during the pandemic, considering five various energy and gold markets, and examining a longer and recent period spanning from November 2017 to November 2022. The empirical results show that, during the pandemic, complexity increased in gold and natural gas markets, stability strongly decreased in WTI and natural gas markets, and irregularity obviously increased in gold market but decreased in all energy markets. Besides, heating oil and gasoline markets appear to be unaffected by the COVID-19 pandemic especially in terms of complexity and stability compared to WTI, Brent, and gas markets. We conclude that the gold market maybe not attractive compared to energy markets for investors and traders during the pandemic. Besides, heating oil and gasoline markets offer interesting investment opportunities during the world economic downturn caused the outbreak of the pandemic.